High prevalence of undetected heart failure in long‐term care residents: findings from the Heart Failure in Care Homes (HFinCH) study. (February 2013) - Hancock, Helen C.; Close, Helen; Mason, James M.; Murphy, Jerry J.; Fuat, Ahmet; Singh, Raj; Wood, Esther; de, Mark; Brennan, Gill; Hussain, Nehal; Kumar, Nitin; Wilson, Doug; et al.
<x xml:space="preserve">Abstract</x> Aims Diagnosis of heart failure in older people in long‐term care is challenging because of co‐morbidities, cognitive deficit, polypharmacy, immobility, and poor access to services. This study aimed to ascertain heart failure prevalence and clinical management in this population. Methods and results A total of 405 residents, aged 65–100 years, in 33 UK care facilities were prospectively enrolled between April 2009 and June 2010. The presence of heart failure was determined using European Society of Cardiology guidelines, modified where necessary for immobility. Evaluation of symptoms and signs, functional capacity, and quality of life, portable on‐site echocardiography, and medical record review were completed in 399 cases. The point prevalence of heart failure was 22.8% [n = 91, 95% confidence interval (CI) 18.8–27.2%]; of these, 62.7% (n = 57, 95% CI 59.6–66.5%) had heart failure with preserved ejection fraction and 37.3% had left ventricular systolic dysfunction (n = 34, 95% CI 34.8–40.5%). A total of 76% (n = 61) of previous diagnoses of heart failure were not confirmed, and up to 90% (n = 82) of study cases were new. No symptoms or signs were reliable predictors of heart failure. Conclusion Heart failure was diagnosed in almost a quarter of residents: the prevalence was substantially higher than in other populations. The majority of heart failure cases were undiagnosed, while three‐quarters of previously recorded cases were misdiagnosed. Common symptoms and signs appear to have little clinical utility in this population. Early, accurate differential diagnosis is key to the effective management of heart failure; this may be failing in long‐term care facilities. Trial registration ISRCTN19781227